Regenerative medicine as applied to general surgery - Orlando, G; Wood, K; De Coppi, P; Baptista, P; Binder, K; Bitar, K; Breuer, C; Burnett, L; Christ, G; Farney, A; Figliuzzi, M; Holmes, J; et al. (2012)
The present review illustrates the state of the art of regenerative medicine (RM) as applied to surgical diseases and demonstrates that this field has the potential to address some of the unmet needs in surgery. RM is a multidisciplinary field whose purpose is to regenerate in vivo or ex vivo human cells, tissues, or organs to restore or establish normal function through exploitation of the potential to regenerate, which is intrinsic to human cells, tissues, and organs. RM uses cells and/or specially designed biomaterials to reach its goals and RM-based therapies are already in use in several clinical trials in most fields of surgery. The main challenges for investigators are threefold: Creation of an appropriate microenvironment ex vivo that is able to sustain cell physiology and function in order to generate the desired cells or body parts; identification and appropriate manipulation of cells that have the potential to generate parenchymal, stromal and vascular components on demand, both in vivo and ex vivo; and production of smart materials that are able to drive cell fate. © 2012 by Lippincott Williams and Wilkins.